The Effect Of Dysmenorrhea On Mood Changes In 2020 Yarsi University Faculty Of Medicine Students And According To Islamic Perspective - Shintya Nabilla Trianti; Endang Purwaningsih; Qomariyah Qomariyah; Firman Arifandi (Junior Medical Journal, 2022)
Background: Dysmenorrhea is defined as painful uterine cramps occurring during menstruation and is one of the most common causes of abdominal pain and menstrual disorders. Not all women who experience menstruation feel comfortable; this is caused by general disturbances such as mood swings, joint pain, and abdominal pain, which is called dysmenorrhea. Women with dysmenorrhea need knowledge about the effects of dysmenorrhea on mood changes. The effect of dysmenorrhea on mood in 2020 YARSI University Faculty of Medicine student is unknown.Methods: This type of research is descriptive-analytic with a cross-sectional study approach. The sample in the study consisted of students from the Faculty of Medicine at YARSI University, class of 2020, with 120 respondents. Data was collected by filling out a questionnaire to measure pain and mood changes, namely Numeric Rating Scale (NRS) and Four Dimensions Mood Scale (FDMS). The analysis was carried out univariately on each variable and bivariate to see the relationship between variables. Results: The results showed that YARSI University Faculty of Medicine students who experienced mild, moderate, and severe dysmenorrhea with negative mood changes, respectively, were 5 people (10.4%), 5 people (10.6%), and 14 people (56%). Mild, moderate, and severe dysmenorrhea with relaxation mood swings affected 10 people (20.8%), 31 people (66%), and 6 people (24%). Mild, moderate, and severe dysmenorrhea with positive mood changes, respectively, affected 33 people (68.8%), 1 person (23.4%), and 5 people (20%). The results of the Chi-Square analysis showed a relationship between the incidence of dysmenorrhea and mood swings.Conclusion: There is a relationship between the incidence of dysmenorrhea and mood swings in 2020 YARSI University Faculty of Medicine students.